Surface disorder in c-Si induced by swift heavy ions - Bogle, Kashinath A.; Gokhale, Suresh P.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2005)
The disorders induced in crystalline silicon (c-Si) through the process of electronic energy loss in the swift heavy ion irradiation were investigated. A number of silicon <100> samples were irradiated with 65 MeV oxygen ions at different fluences, 1x10(13) to 1.5x10(14) ions/cm(2), and characterized by the Raman spectroscopy, the optical reflectivity, the X-ray reflectivity, the atomic force microscopy (AFM) and the X-ray diffraction (XRD) techniques. The intensity, redshift, phonon coherence length and asymmetric broadening associated with the Raman peaks reveal that stressed and disordered lattice zones are produced in the surface region of the irradiated silicon. The average crystallite size, obtained by analyzing Raman spectrum with the phonon confinement model, was very large in the virgin silicon but decreased to <100 nm dimension in the ion irradiated silicon. The results of the X-ray reflectivity, AFM and optical reflectivity of 200-700 nm radiation indicate that the roughness of the silicon surface has enhanced substantially after ion irradiation. The diffusion of oxygen in silicon surface during ion irradiation is evident from the oscillation in the X-ray reflectivity spectrum and the sharp decrease in the reflectivity of 200-400 nm radiation. The rise in temperature, estimated from the heat spike model, was high enough to melt the local silicon surface. The results of XRD indicate that lattice defects have been induced and a new plane <211> has been formed in the silicon <100> after ion irradiation. The results of the present study show that the energy deposited in crystalline silicon through the process of electronic energy loss similar to 0.944 keV/nm per ion is sufficient to induce disorders of appreciable magnitude in the silicon surface even at a fluence of similar to 10(13) ions/cm(2).
Keywords: AFM; crystalline silicon; ion irradiation; optical and X-ray reflectivity; Raman; XRD

Synthesis of cube-shaped gold nanostructures by electron irradiation - Dhumale, Vinayak A.; Gangwar, Rajesh K.; Shah, Preeti V.; Bhoraskar, Vasant N.; Mulla, Imtiaz S.; Sharma, Rishi B. (Materials Letters, 2011)
The needle-like gold nanostructures were synthesized by using chloroauric acid (HAuCl(4)) as a metal precursor and sodium borohydride (NaBH(4)) as the reducing agent. These needle-like nanostructures of gold were irradiated with high energy electrons (E-6 MeV, phi similar to 10(12) e cm(-2) s(-1)). The pre- and post-irradiated gold nanostructures were characterized by Scanning Electron Microscopy (SEM), UV-vis spectroscopy, X-ray Diffraction (XRD) and contact angle measurement (GBX-Model Digidrop) techniques. The results of the SEM revealed that after electron irradiation, the needle-like gold structures got fragmented into identical cube-shaped gold nanostructures, though of different sizes. The XRD analysis indicated that the average crystallite size of the gold nanostructures remained unchanged even after irradiation with high energy electrons. A glass surface showed hydrophilic behavior when coated with needle-like nanostructures and became ultra hydrophilic when coated with cube-shaped gold nanostructures. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Gold nanostructures; High energy electron irradiation; Nanostructured materials; Radiation damage; Surfaces; Ultra hydrophilic surfaces